Assembly line productivity improvement through TPM by controlling line organisation efficiency and out of balance index: an empirical exploration. (5th May 2022) - Gupta, Pardeep; Mittal, Ankesh; Hooda, Aman; Gupta, Niharika
The present study aims to examine the role of implementing TPM in improving the assembly line productivity of an automobile manufacturing industry. The organisation started implementing TPM to improve plant productivity by maintaining equipment, workplace layout improvement, and increasing employee morale. The case study data for this study has been collected after having discussions with TPM team members and reading the TPM reports and result sheets available with the industry. The TPM team recognised a significant scope of an improvement in fuel tanks productivity. The efforts were made to reduce the line stoppages, perform line balancing and carry out operations standardisation. As a result of these initiatives, the fuel tank assembly line's productivity enhanced from 140 to 158 units per shift within 14 months. This study is an innovative case study that demonstrates the effectiveness of TPM initiatives in enhancing the productivity of an assembly line in the Indian automobile industry.